Psychosocial components of cardiac recovery and rehabilitation attendance - King, K (2001)
OBJECTIVE—To examine the relations between demographic factors, specific psychosocial factors, and cardiac rehabilitation attendance. DESIGN—Cohort, repeated measures design. SETTING—A large tertiary care centre in western Canada PATIENTS—304 consecutive consenting patients discharged following acute myocardial infarction and/or coronary artery bypass graft surgery. MAIN OUTCOME MEASURES—The Jenkins self-efficacy expectation scales and activity checklists of behaviour performance for maintaining health and role resumption, modified version of the self-motivation inventory, and the shortened social support scale. RESULTS—Those who had higher role resumption behaviour performance scores at two weeks after discharge were significantly less likely to attend cardiac rehabilitation programmes. At six months after discharge, those who attended cardiac rehabilitation demonstrated higher health maintenance self-efficacy expectation and behaviour performance scores. Health maintenance self-efficacy expectation and behaviour performance improved over time. Women reported less social support but showed greater improvement in health maintenance self-efficacy expectation. Changes in self-efficacy scores were unrelated to—but changes in health maintenance behaviour performance scores were strongly associated with—cardiac rehabilitation attendance. CONCLUSIONS—Cardiac patients and practitioners may have misconceptions about the mandate and potential benefits of rehabilitation programmes. Patients who resumed role related activities early and more completely apparently did not see the need to "rehabilitate" while those who attended cardiac rehabilitation programmes enhanced their secondary prevention behaviours.   Keywords: self-efficacy; motivation; social support; cardiac recovery; cardiac rehabilitation